Experimental study on the aeration performance of water jet which is performed by a venturi device - Koçyiğit, Şermin; Emıroglu, Muhammet Emin (My University, 2024)
The purpose of aeration in water is to transfer or remove gases from the water. Dissolved oxygen is critical for living life. In water engineering, aeration and oxygen transfer using water jets are common. In this study, various venturi nozzles with air holes in the throat portion were manufactured and meaningful experiments were conducted to determine their oxygen transfer efficiency and aeration performance., the venturi nozzles with throat diameters 14, 17 and 20 mm were used in the experimental study. The ratio of the diameter of the air holes to the diameter of the throat portion is taken as 0.1, 0.2 and 0.3. Different experiments were carried out for nine different hole diameters. In addition, the ratio of the throat portion length to the throat portion diameter was taken as 1.00 and 0.50. In addition, comprehensive experiments were carried out by considering the ratio of outlet length to outlet diameter for all nozzles, 1 and 2, and for one venturi, 1, 2, 3, 4 and 5. The experiments were also conducted for the circular nozzle to make comparisons. In this study, venturi nozzles gave better results than circular nozzles, and higher aeration performance values were obtained for the ratios 0.2 and 0.3, 1, 0.50 and 0.50. It was found that the aeration performance of the venturi nozzle was approximately 6.5 times higher than the air entrainment rate performance of the circular nozzle and 2.5 times higher in terms of oxygen transfer.
Keywords: Aeration; Water jet; venturi; oxygen transfer; nozzle